Low frequency of acute hepatitis E virus (HEV) infections but high past HEV exposure in subjects from Cambodia with mild liver enzyme elevations, unexplained fever or immunodeficiency due to HIV-1 infection - Nouhin, Janin; Barennes, Hubert; Madec, Yoann; Prak, Sophearot; Hou, Serey Vannak; Kerleguer, Alexandra; Kim, Saorin; Pean, Polidy; Rouet, François (Journal of clinical virology, 2015)
•HEV infection was retrospectively assessed in 825 Cambodian subjects.•We found an overall anti-HEV IgM prevalence rate of 1.1%.•No subject tested positive for HEV RNA.•A high (30%) anti-HEV IgG prevalence rate was obtained.•Recent HEV infections were rare, contrasting with a high level of past HEV exposure. In Cambodia, previous studies conducted on hepatitis E virus (HEV) infection are scant, sometimes old, and showed inconsistent results. Moreover, there is no data about HEV infection in Cambodian HIV-1-infected patients. To assess the occurrence of acute HEV infections and the level of past HEV exposure in one Mekong country. Using anti-HEV IgM and HEV RNA detection, we retrospectively investigated the presence of acute HEV infection in 825 individuals, including 350 subjects with or without fever, 300 subjects with or without liver enzyme elevations (LEE) and 175 antiretroviral treatment (ART)-naïve, severely immunocompromised HIV-1-infected patients. The detection of anti-HEV IgG was also performed to assess ancient HEV exposure. Nine individuals tested positive for anti-HEV IgM yielding an overall rate of 1.1% (95% confidence interval (CI), 0.5–2.0). We did not find significant differences for anti-HEV IgM rates between subjects with unexplained fevers (1.5%) and those with malaria or dengue-associated fever (1.7%) or non-febrile individuals (0%) (P=0.49), and between subjects with (1.5%) and without (2.0%) LEE (P=0.87). No HIV-infected patient tested positive for anti-HEV IgM. HEV RNA was not detected in all tested plasma specimens (n=578). Overall, the anti-HEV IgG prevalence rate was 30.1% (95% CI, 27.0–33.2). The scarcity of recent HEV infection contrasted with the high level of past HEV exposure. The role of HEV in liver disease is likely minor in Cambodia since no HEV RNA was detected in our studied populations, including HIV-positive patients with severe immunodepression.